Genetic diversity, ancestry relationships and consensus among phenotype and genotype in banana (Musa acuminata) clones from Aormosa (Argentina) farmers - Ermini, José Luis (2016)
Though banana is a tropical crop, the Argentinean Northeastern Province of Formosa has extensively promoted its production. Genetic variation was assessed by the Amplified Fragment Length Polymorphism (AFLP) in a set of allotriploid and autotriploid clones from Formosa farms. Clones were also evaluated for perimeter and height of the pseudo-stem, number of leaves before flowering, number of flower clusters and length of fruits. Four international autotriploid varieties were used as samples. An AMOVA test widely discriminated among allotriploid clones, autotriploid clones and check varieties. The ancestry relationships between the autotriploids genotypes verified that clones were derived from the check varieties. Principal Coordinates Analysis was applied to assess the genetic diversity, demonstrating that 45% of the total molecular variation was explained by the three first principal coordinates. The first two principal components explained 77% of total phenotypic variability according to a Principal Components Analysis with the mean phenotypic values of clones and check varieties. Procrustes Analysis verified a high consensus (71.3%) among phenotypic and genotypic characterizations, suggesting that putative associations could be found among both sets of data. The 79.6% of the total variation was explained by the two principal components in this Procrustes Analysis.